2021
DOI: 10.1001/jamaoncol.2020.6758
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Osimertinib Plus Bevacizumab vs Osimertinib in Patients With EGFR T790M–Mutated Non–Small Cell Lung Cancer Previously Treated With Epidermal Growth Factor Receptor–Tyrosine Kinase Inhibitor

Abstract: IMPORTANCE Although treatment with first-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) plus antiangiogenic inhibitor has shown promising efficacies in patients with EGFR-mutated lung adenocarcinoma, recent single-arm studies have suggested that osimertinib plus antiangiogenic inhibitor might not work synergistically. OBJECTIVE To explore the efficacy and safety of osimertinib plus bevacizumab compared with osimertinib alone in patients with lung adenocarcinoma with EGFR T79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 26 publications
5
140
2
Order By: Relevance
“…Recently in a phase 2 study, the addition of bevacizumab to osimertinib was not shown to be beneficial in previously treated EGFR TKIs patients with the T790M mutation. 132 …”
Section: Discussionmentioning
confidence: 99%
“…Recently in a phase 2 study, the addition of bevacizumab to osimertinib was not shown to be beneficial in previously treated EGFR TKIs patients with the T790M mutation. 132 …”
Section: Discussionmentioning
confidence: 99%
“…with EGFR-TKI and cetuximab could be a reasonable strategy for treating patients with EGFR-mutant lung cancer, clinical trials have failed to show that the combination of afatinib and cetuximab is superior to afatinib monotherapy (15). EGFR-TKIs have been successfully combined with anti-angiogenic agents such as bevacizumab or ramucirumab to treat patients with lung cancer harboring EGFR mutations (12,14); however, a recent randomized clinical trial revealed that the combination of osimertinib and bevacizumab failed to show superior progression-free survival compared to osimertinib monotherapy (29). Multiple negative predictive biomarkers have been reported for the effect of EGFR-TKIs (6-11); however, the predictive factor for combination therapies including EGR-TKIs and bevacizumab has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent phase III randomized clinical trials demonstrated a longer median PFS in patients who received erlotinib and bevacizumab versus patients who received erlotinib monotherapy (16.9 vs. 13.3, p = 0.016); however, final OS analysis did not demonstrate a benefit with the addition of bevacizumab [102,103]. In addition, a recent phase II randomized clinical trial failed to demonstrate improved median PFS in patients with EGFR-mutated lung adenocarcinoma harboring T790M who progressed on prior early generation EGFR TKIs and were randomized to either osimertinib versus osimertinib plus bevacizumab [104].…”
Section: Combining Vegf/vegfr2-directed Monoclonal Antibodies and Egfr Tkismentioning
confidence: 98%